THE EFFECT OF RESITATION LEARNING METHOD ON LEARNING RESULT OF X CLASS IN FUNGI MATERIAL - Kurratul 'Aini; Muhammad Isnaini; Erie Agusta; Rini Anggraini (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This research aims to know the effect of resitation learning methods to cognitive learning results of students on Fungi material in the X class in one of senior high school in Palembang. Research method in this research is a quasi experimental with non-equivalent control group design research design. The technique of sampling is using the saturated sampling technique. The instruments used in this research are a test to measure the students' understanding of the cognitive basis with categories reserved C1-C4. Based on the results of data analysis using t-test obtained results that there is a difference of the second posttest average group retrieved value amounted to 5,328 whereas significant extent values by 5%. This shows that the alternative hypothesis was received and zero hypothesis was rejected. This indicates that resitation learning method effects on cognitive learning result of students on the fungi material. Keywords: cognitive, learning methods, material, fungi resitation, the results of the study